2016
DOI: 10.4102/sajce.v6i1.411
|View full text |Cite
|
Sign up to set email alerts
|

Teachers’ perceptions of the quality of the new Expressive Arts textbooks for Malawi primary schools

Abstract: <p>The national government in Malawi implemented an outcomes-based curriculum reform in 2007. To facilitate implementation, new textbooks were developed for the primary school curriculum. This study intended to explore teachers’ use and perception of the new Expressive Arts textbooks. The participants consisted of 192 Expressive Arts teachers, grades 5–8, selected by purposeful sampling. Data were collected through questionnaires and semistructured interviews. It was found that teachers believed that the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 9 publications
(15 reference statements)
0
13
0
Order By: Relevance
“…This could be adduced to the fact that graphics are concise and memorable, and they make relationships within the information readily apparent, thereby helping in elaborating or expanding different concepts (Aggarwal 2001;Widodo 2007). However, Chirwa and Naidoo (2016) also contend that the cluttering of the textbook with irrelevant distracting features may reduce the effectiveness of the text. Nonetheless, in accounting, there is a need for textbooks to contain a reasonable number of features such as balance sheets, income statements and other types of financial figures to aid the instruction and to consolidate learning.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This could be adduced to the fact that graphics are concise and memorable, and they make relationships within the information readily apparent, thereby helping in elaborating or expanding different concepts (Aggarwal 2001;Widodo 2007). However, Chirwa and Naidoo (2016) also contend that the cluttering of the textbook with irrelevant distracting features may reduce the effectiveness of the text. Nonetheless, in accounting, there is a need for textbooks to contain a reasonable number of features such as balance sheets, income statements and other types of financial figures to aid the instruction and to consolidate learning.…”
Section: Discussionmentioning
confidence: 99%
“…Extant literature has shown that textbooks are regarded as effective tools to ensure better quality in terms of instruction and content (Chirwa & Naidoo 2016;DoE 2009;Freahat & Smadi 2014;Gök 2012;Nasser & Oqlah 2014;Swanepoel 2010;Tarman & Kuran 2015). However, high-quality teaching is dependent on the availability of quality and appropriate resources.…”
Section: Good-quality Textbooksmentioning
confidence: 99%
See 3 more Smart Citations